Software Quality Evaluation Of MV5PAS Airport Authority Region III Using FURPS Model: Software Quality Evaluation Of MV5PAS Airport Authority Region III Using FURPS Model - Suhartono, Darell Timotius; Indriyanti, Aries Dwi (Universitas Negeri Surabaya, 2025)
The widespread use of software to enhance organizational efficiency makes software development essential. The Airport Authority Region III Office uses MV5PAS software for operational activities, aiming to improve public services. Ensuring software quality is crucial for optimal performance, which this study evaluates using the FURPS model. This model assesses software based on five characteristics: functionality, usability, reliability, performance, and supportability.The study employs a mixed-method evaluation approach. Functionality and usability are assessed via a questionnaire with 25 respondents, while reliability is tested using WAPT V.10.1. Performance is measured with GTMetrix web analysis, and supportability is tested across different OS and browsers.Results indicate that MV5PAS meets the FURPS model standards in four categories. Functionality scores 0.983 (0 ≤ X ≤ 1), reliability achieves R = 0.982, usability scores 80.2, and supportability is confirmed through successful multi-device testing. However, performance requires improvement, receiving a “D” on the GTMetrix Grade. This highlights the need for quality enhancements to optimize the system’s overall efficiency.